Estudo da atividade inibidora do sistema do complemento humano presente na saliva e conteúdo intestinal de Lutzomyia longipalpis (Diptera: Psychodidae) - Vladimir Fazito do Vale (2011)
The complement system plays an important role in both innate and adaptive immunity, mainly by the opsonization of invading organisms, anaphylatoxin production and pore formation in the surface of pathogens. The saliva of Lutzomyia longipalpis, the main vector of Leishmania infantum in Americas, is able to inhibit both the classical and alternative pathways of the human complement system. This study aimed to increase knowledge concerning complement inhibition by L. longipalpis. In relation to the classical pathway, L. longipalpis saliva did not inhibit the deposition of the first complement component, C1q. However, a strong inhibition on C4b, C3b, C5b and C9 deposition occurred in the presence of saliva. Membrane attack complex formation was not directly affected by saliva, indicating inhibition in the early steps of the cascade. Salivary gland extract was able to inhibit C4 cleavage, but not to inhibit the enzymatic activity of C1s. The mechanism of action of the Lutzomyia longipalpis saliva seems to be related to the presence of a salivary protein capable of binding human C1q. This salivary protein responsible for classical pathway inhibition was identified as being LJM19, a 11 kDa protein that is found in sandfly saliva as a 22.3 kDa dimer. Alternative pathway inhibition was also related to the early steps of the complement cascade. Salivary gland extract was able to inhibit C3b, factor Bb, C5b and C9 deposition. Inhibition of the alternative pathway was related to the capacity of saliva to avoid factor B cleavage. Nevertheless, the saliva of L. longipalpis was not able to directly inhibit factor D activity. The activity of intestinal contents was also tested in deposition assays. In this case, no inhibition of the alternative pathway was found for C5b. For the classical pathway, the intestinal contents of L. longipalpis inhibited the deposition of C3b and C5b, without inhibiting C4b deposition. The presence of complement inhibitors in the saliva and midgut of sandflies should be related to the protection of the intestinal epithelium against the lytic effects of the ingested blood. In addition, complement inhibition might protect the salivary proteins from an immunologic response directed against the salivary antigens. It is well documented that C3b opsonization increases considerably the immunogenicity of antigens, even though the soluble ones such as the salivary proteins